International Volunteerism and Capacity Development in Nonprofit Organizations of the Global South. (April 2020) - Schech, Susanne; Skelton, Tracey; Mundkur, Anuradha; Kothari, Uma
Although international volunteerism has been a part of official development assistance for decades, the capacity development (CD) impacts of such programs in nonprofit organizations (NPOs) in the Global South have received scant attention. This article provides insights into the ways international volunteerism contributes to endogenous CD processes by analyzing survey and interview data collected from Australian volunteers and their host organizations in four countries. It shows that volunteers' contributions can be usefully examined through the lens of Baser and Morgan's framework of five core capabilities: to carry out tasks, to relate and attract support, to adapt and renew, to balance diversity and coherence, and to commit and engage. Although the voluntary nature of the relationship between host organization and volunteer can make CD impacts less predictable and controllable, it also affords time to explore and negotiate what contributions are most useful to an organization within a specific context.